2015
DOI: 10.1038/srep17737
|View full text |Cite
|
Sign up to set email alerts
|

Lipidomics comparing DCD and DBD liver allografts uncovers lysophospholipids elevated in recipients undergoing early allograft dysfunction

Abstract: Finding specific biomarkers of liver damage in clinical evaluations could increase the pool of available organs for transplantation. Lipids are key regulators in cell necrosis and hence this study hypothesised that lipid levels could be altered in organs suffering severe ischemia. Matched pre- and post-transplant biopsies from donation after circulatory death (DCD, n = 36, mean warm ischemia time = 21min) and donation after brain death (DBD, n = 76, warm ischemia time = none) were collected. Lipidomic discover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 48 publications
(57 reference statements)
2
23
0
Order By: Relevance
“…Subsequently, ROS production after reperfusion is greater and more pronounced leading to increased cellular injury. 33 These mechanisms help explain the clinical observation as to why steatotic allografts and those from NHBD are at higher risk for early allograft dysfunction ( Figure 5).…”
Section: Reactive Oxygen Species and Inflammatory Cytokinesmentioning
confidence: 97%
See 2 more Smart Citations
“…Subsequently, ROS production after reperfusion is greater and more pronounced leading to increased cellular injury. 33 These mechanisms help explain the clinical observation as to why steatotic allografts and those from NHBD are at higher risk for early allograft dysfunction ( Figure 5).…”
Section: Reactive Oxygen Species and Inflammatory Cytokinesmentioning
confidence: 97%
“…NHBD donor livers demonstrate increased levels of ceramide18, a pro‐apoptotic activator correlating with increased cell death from IRI. VWF is also elevated in NHBD donor livers indicating higher risk of microthrombi formation and loss of sinusoidal blood flow contributing to ongoing IRI during organ recovery …”
Section: Clinical Context Of Iri In Liver Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review on the use of metabolomics to discover liver biomarkers for transplantation outcomes in liver tissue biopsies highlighted promising results [17]. These first studies identified lipid molecules [18][19][20], tryptophan, kynurenine and S-adenosylmethionine as liver biomarkers [21,22].…”
Section: Of 13mentioning
confidence: 99%
“…Furthermore, analyses of human bile during liver transplantation by capillary electrophoresis showed distinct metabolic fingerprints in donors and recipients [8]. Whereas more recent publication has been focussed on much larger group of liver grafts belonging to two distinct organ donor sources, namely the cadaveric donation after circulatory death (DCD), and donation after brain death (DBD) and applied lipidomics studies identify markers of early allograft dysfunction [9]. …”
Section: Introductionmentioning
confidence: 99%